A Real-World Study of Prognosis of N0M0 Hepatocellular Carcinoma with Hepatic Resection Based on SEER Database - Guangxi Zhu; Wensheng Wang; Qin Liu; Dongfeng Chen; Liangzhi Wen (Gastroenterology Research and Practice)
Aim. To develop and validate a simple-to-use nomogram for prediction of 3-/5-year survival in patients with N0M0 hepatocellular carcinoma after curative liver resection. Patients and Methods. Patients diagnosed HCC with hepatic resection in the Surveillance, Epidemiology, and End Results (SEER) database were included to identify prognostic factors of overall survival. Multivariate Cox regression were used to create a nomogram. Results. We identified 4856 HCC with hepatic resection from the SEER database. A nomogram to predict long-term survival with a C-index 0.667 (95% CI, 0.653 to 0.681) is more efficient than TNM staging with a lower C-index 0.613 (95% CI, 0.597 to 0.629). The C-index was confirmed to be 0.663 (95% CI, 0.640 to 0.686) through validation, suggesting a good discrimination and a good prediction capability. Conclusions. The nomogram is a simple and effective screening tool for assessing the prognosis of HCC with hepatic resection and assists with the planning of individual postoperative surveillance protocols.